Unveiling the mechanism of photoinduced isomerization of the photoactive yellow protein (PYP) chromophore - Gromov, Evgeniy (The journal of chemical physics, 2014)
A detailed theoretical analysis, based on extensive ab initio second-order approximate coupled cluster calculations, has been performed for the S1 potential energy surface (PES) of four photoactive yellow protein (PYP) chromophore derivatives that are hydrogen bonded with two water molecules and differ merely in the carbonyl substituent. The main focus is put on contrasting the isomerization properties of these four species in the S1 excited state, related to torsion around the chromophore's single and double carbon-carbon bonds. The analysis provides evidence of the different isomerization behavior of these four chromophore complexes, which relates to the difference in their carbonyl substituents. While a stable double-bond torsion pathway exists on the S1 PES of the chromophores bearing the -O-CH3 and -NH2 substituents, this is not the case for the -S-CH3 and -CH3 substituted species. The presence of the -S-CH3 group leads to a strong instability of the chromophore with respect to the single-bond twist, whereas in the case of the -CH3 substituent a crossing of the S1 and S2 PESs occurs, which perturbs the pathway. Based on this analysis, the key factors that support the double-bond torsion have been identified. These are (i) the hydrogen bonds at the phenolic oxygen of the chromophore, (ii) the weak electron-acceptor character of the carbonyl group, and (iii) the ethylene-like pattern of the torsion in the beginning of the process. Our results suggest that the interplay between these factors determines the chromophore's isomerization in the solvent environment and in the native PYP environment.
Gesehen am 20.10.2020